A Study to Investigate Irish Primary School Teachers Perceptions and Approaches to Differentiation in Mathematics. - Conaty, Kathy (Marino Institute of Education, 2021)
Development in education in the 21st century has created many changes for teachers. There is a significant increase in diverse learning needs in Irish primary classrooms. Teachers are responsible for catering to these learners in line with legislation and policy implementation such as the Education Act of 1998 and the Department of Education 2017. This small-scale research study explores Irish primary school teachers perceptions and approaches to differentiation in mathematics. The main objective of the research study explores perspectives, strategies, and challenges faced by primary school teachers employing differentiation in maths in their classrooms. This research study employs a qualitative research method, through nine semi-structured interviews with Irish primary teachers contributing considerably to the research. The data was then collected, and analysis of the data was conducted using a thematical framework. Findings from the analysis of the data revealed the increased recognition of differentiation in maths education. Teachers express the significance of differentiation and their role as teachers to cater for all learners. The findings identify mixed views on strategies such as mixed ability and ability group, withdrawal, and in-class support. It emerged that teachers believe they do not receive sufficient training in college on differentiation, particularly in the area of mathematics. This research found that a large student-teacher ratio can negatively impact a teachers ability to apply effective differentiation in maths. This resulted in the introduction of station teaching for many participants. The findings suggest that teachers would benefit from more CPD opportunities to support teachers in the area of differentiation in maths. This potentially could be implemented through the revised curriculum as it brings opportunity for updating differentiation instruction. This research study investigates teachers lived experiences, opinions, and attitudes while building on the existing knowledge that exists from preceding studies.
Keywords: Irish Primary Schools; Student-teacher ratio; Education Act of 1998; Mathematics; Learners; Training; Primary education; Ireland; Inclusive learning; Training; Mathematics